2017
DOI: 10.1038/modpathol.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of follicular dendritic cell sarcoma by molecular inversion probe array reveals tumor suppressor-driven biology

Abstract: Follicular dendritic cell sarcoma is a rare malignant neoplasm of dendritic cell origin that is currently poorly characterized by genetic studies. To investigate whether recurrent genomic alterations may underlie the biology of follicular dendritic cell sarcoma and to identify potential contributory regions and genes, molecular inversion probe array analysis was performed on 14 independent formalin-fixed, paraffin-embedded samples. Abnormal genomic profiles were observed in 11 out of 14 (79%) cases. The majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 27 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Genomic DNA was processed for molecular inversion probe array analysis using the OncoScan FFPE Assay kit (ThermoFisher, Santa Clara, CA, USA), as described (Paxton et al, 2015). Data analysis was performed using Chromosome Analysis software (ChAS) version 3.1 (ThermoFisher) and Nexus Express Software for OncoScan version 3.1 (Biodiscovery, Hawthorne, CA, USA) with reference to assembly GRCh37/hg19, as described (Andersen et al, 2017). All cases were processed using the TuScan segmentation algorithm except for case MG88, which was re-centered and processed using SNP-FASST2.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was processed for molecular inversion probe array analysis using the OncoScan FFPE Assay kit (ThermoFisher, Santa Clara, CA, USA), as described (Paxton et al, 2015). Data analysis was performed using Chromosome Analysis software (ChAS) version 3.1 (ThermoFisher) and Nexus Express Software for OncoScan version 3.1 (Biodiscovery, Hawthorne, CA, USA) with reference to assembly GRCh37/hg19, as described (Andersen et al, 2017). All cases were processed using the TuScan segmentation algorithm except for case MG88, which was re-centered and processed using SNP-FASST2.…”
Section: Methodsmentioning
confidence: 99%
“…28 Data analysis was performed with Chromosome Analysis software (ChAS), version 3.2 (Thermo Fisher), and Nexus Express Software for OncoScan, version 3.1 (BioDiscovery, Hawthorne, CA), with reference to assembly GRCh37/hg19, by a published method. 29 All cases were processed with the TuScan segmentation algorithm (ChAS; Thermo Fisher), except for case PS02, which was recentered and processed by using SNP-FASST2 (OncoScan; Nexus Express). Recurrent genomic alterations were calculated with the aggregate analysis in Nexus Express.…”
Section: Copy Number Aberrationsmentioning
confidence: 99%
“…A tumor suppressor‐driven biology has also been suggested in FDCS. Andersen et al studied genomic alterations of 14 FDCS and found that the majority (11) showed hemizygous deletions affecting multiple chromosomes and involving tumor suppressor genes DKN2A, RB1, BIRC3, and CYLD 26 …”
Section: Discussionmentioning
confidence: 99%